An Overview of Current Commercial Fashion Photography - Rafiqi, Hindam Basith (Bina Nusantara University, 2022)
The presence of smartphones today has an impact on commercial photography, especially fashion photography. The presence of smartphones makes everyone able to become a commercial fashion photographer, which makes the role of a commercial fashion photographer even more questionable. Departing from this phenomenon this research was conducted. This research is a research with descriptive qualitative method. This study was conducted to describe the phenomenon of commercial fashion photography that is currently happening. In addition, this phenomenon can produce an idea for commercial fashion photographers in dealing with the world of commercial fashion photography today. The result of this research is that today's commercial fashion photographers need to have out of the box ideas which are the qualities of ideas and concepts that distinguish them from other commercial fashionphotographers. Although the need for tools in the process of creating photography today can be replaced with smartphones, the quality of ideas and concepts is something that is not necessarily owned by every commercial fashion photographer.